Measuring the Usability of a Smartphone Delivered Museum Guide - Mohd Kamal, Othman; Petrie, Helen; Power, Christopher (2013)
Smartphones are increasingly being deployed by museums and other cultural spaces to provide guides for visitors, replacing dedicated audioguides or docents. This paper describes a study investigating a scale to measure the usability of a multimedia smartphone guide for a museum, the Multimedia Guide Scale (MMGS). Two different types of museum guide were compared: a free choice tour (FC-tour) and guided tour (G-tour). Result shows that there was a significant difference in scores on the MMGS between the two tours, between the three components of the MMGS (Quality of Interaction; Learnability and Control; General Usability) and a significant interaction between the two variables (factors and the guides). The mean scores were higher for the G-tour on the General Usability component and particularly on the Quality of Interaction component, whereas for the Learnability and Control component, scores were higher for the FC-tour Guide. The implications of these findings and the use of the MMGS are discussed.